2020
DOI: 10.3846/bme.2020.12189
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Organizational Support and Proactive Personality on Affective Commitment: Mediating Role of Prosocial Motivation

Abstract: Purpose – The main objective of this study is to examine the effect of perceived organizational support and proactive personality on prosocial motivation. Furthermore, it looks upon the influence of prosocial motivation on affective commitment. The indirect effect of perceived organizational support and proactive personality on affective commitment through prosocial motivation is also examined. Research methodology – The self-administered survey questionnaires are utilised for collecting the data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 113 publications
0
15
0
2
Order By: Relevance
“…Studies on affective commitment based on social exchange theory have found that one important influencer of affective commitment is POS, and this effect can be direct [60,84] in both banking and trade sectors, or indirect [80,85] in banking and education sectors. Based on what has proposed above, the researchers hypothesized the following:…”
Section: Pos and Affective Commitmentmentioning
confidence: 99%
“…Studies on affective commitment based on social exchange theory have found that one important influencer of affective commitment is POS, and this effect can be direct [60,84] in both banking and trade sectors, or indirect [80,85] in banking and education sectors. Based on what has proposed above, the researchers hypothesized the following:…”
Section: Pos and Affective Commitmentmentioning
confidence: 99%
“…Organizations expect commitment from workers in order to decrease expenses and improve performance and provision of product quality [ 56 ]. This commitment can be improved by building beliefs, cooperation, and employee empowerment.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Management support for the community. Ullah et al (2020) research results indicate that perceived organizational support and proactive personality are the drivers of prosocial motivation. Organizations should always provide support for their employees that encourage them to show more desire to help their colleagues in the working environment and foster their commitment towards their organization.…”
Section: Collaboration Between the Different Levels Of Management And The Academic Communitymentioning
confidence: 83%
“…Communication covered explaining solutions, exchanging good practices, ensuring a positive psychological climate, and maintaining team spirit, and established traditions to show that the community might always expect support. Ullah et al (2020) notice that a focus on motivated employees is very important because pro-socially motivated employees are a source of higher performance and productivity. Erum et al (2019) propose that called employees flourish at the workplace and are more engaged in their work.…”
Section: Collaboration Between the Different Levels Of Management And The Academic Communitymentioning
confidence: 99%